S95 Exploiting the immunoregulatory role of Siglec-E via sialic acid-functionalised nanoparticles as a novel approach for the treatment of acute lung injury. (14th November 2013) - Greene, MK; Spence, S; Fay, F; Small, D; Schmid, D; Jaworski, J; Burrows, JF; O'Kane, CM; Kissenpfennig, A; McAuley, DF; Scott, CJ
Abstract : Acute Lung Injury (ALI) is a life-threatening disorder underpinned by dysregulated inflammatory cascades, with resultant injury to lung architecture. Currently, provision of supportive care represents the mainstay of treatment for ALI and novel anti-inflammatory therapeutic strategies are urgently required. We have developed a polymeric nanoconstruct surface-functionalised with sialic acid targeting moieties (SNP), exploiting the anti-inflammatory effects arising from the targeted engagement of Siglec-E receptors on activated macrophages, with potential therapeutic utility in ALI. Polylactic-co-glycolic acid (PLGA) nanoparticles of uniform size distribution (approximately 150nm in diameter) were synthesised in accordance with a salting-out formulation. Intratracheal instillation of 20μg lipopolysaccharide (LPS) was utilised as a model of ALI in C57BL/6 mice, co-administered with 1μg SNP or non-functionalised nanoparticles (NP). Bronchoalveolar lavage (BALF) samples were collected 24 hours after treatment for analysis by enzyme-linked immunosorbent assay (ELISA). As exemplified in Figure 1 ., intratracheal instillation of SNP significantly attenuated BALF levels of pro-inflammatory TNFα and IL-6 cytokines, in addition to the neutrophil chemoattractant KC. Moreover, BALF differential cell counts revealed a decrease in neutrophil numbers upon treatment with SNP under LPS-induced pro-inflammatory conditions. Further analyses addressing the therapeutic utility of SNP have been undertaken, including lung wet/dry ratios, histology and toxicological evaluation, with promising outcomes. This research clearly demonstrates the ability of SNP to diminish the inflammatory response in a murine model of LPS-induced ALI. Considering that chemoattractants and cytokines are key mediators in the pathogenesis of ALI, these results substantiate the credibility of this nanoscaffold as a therapy for ALI. Ultimately, we aim to progress this modality to a human setting, specifically analysing its effects on alveolar macrophages isolated from human volunteers, before advancing to a human ex vivo lung perfusion model.